CD47 Blockade Accelerates Blood Clearance and Alleviates Early Brain Injury After Experimental Subarachnoid Hemorrhage - Xu, Chao-ran; Li, Jian-ru; Jiang, Shao-wei; Wan, Liang; Zhang, Xin; Xia, Lei; Hua, Xu-ming; Li, Shi-ting; Chen, Huai-jun; Fu, Xiong-jie; Jing, Chao-hui (Frontiers in Immunology, 2022)
Aims： Subarachnoid hemorrhage (SAH) is a devastating stroke subtype. Following SAH, erythrocyte lysis contributes to cell death and brain injuries. Blockage of the anti-phagocytic receptor Cluster of Differentiation 47 (CD47) enhances phagocyte clearance of erythrocytes, though it has not been well-studied post-SAH. The current study aims to determine whether anti-CD47 treatment can enhance blood clearance after experimental SAH. Methods： The prechiasmatic blood injection model of SAH was used in mice. Mice were either treated with the CD47-blocking antibody or IgG as control. The effect of the anti-CD47 antibody on blood clearance and neurological function following SAH was determined. Neuroinflammation and neuronal injury were compared between the treatment and control samples on day 1 and day 7 after SAH using flow cytometry, immunofluorescence, Fluoro-Jade C, and Nissl staining, RT-PCR, and Western blot analysis. Results： CD47-blocking antibody sped-up blood clearance after SAH, and resulted in less neuronal injury and neurological deficits than control samples. Microglia played a role in the anti-CD47 blockade. Following SAH Following SAH, CD47 antibody-treated mice had less neuroinflammation and lower levels of apoptosis compared to controls Conclusions： CD47 antibody treatment has a neuroprotective effect following SAH, by increasing blood clearance rate and reducing brain injury. These findings suggest CD47 antibody treatment may improve SAH patient outcomes.